Waterproof, oil-resistant, high-stripping and environment-friendly shoe material and preparation method thereof
Through silane coupling agent pretreatment and surround airflow ultrasonic atomization technology, the problem of insufficient waterproof and oil-proof performance of high-peel shoe materials is solved, and higher waterproof and oil-proof effect and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510241777.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-18
AI Technical Summary
The existing high-release shoe materials have shortcomings in waterproof and oil-proof performance, and their production processes lack effective surface treatment processes or functional additives, resulting in unstable waterproof and oil-proof effect.
The polyethylene terephthalate-based cloth is pretreated with a silane coupling agent to form a polyurethane coating, and the surface is treated by ultrasonic atomizing around the airflow to enhance waterproof and oil-proof performance.
It significantly improves the waterproof and oil-resistant properties of the shoe material, and enhances its mechanical properties, such as tensile strength, tear strength and wear resistance.
Smart Images

Figure CN119843501A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthetic leather, and in particular to a waterproof, oil-proof, highly peelable and environmentally friendly shoe material and a preparation method thereof. Background Art
[0002] With the continuous expansion of the global footwear consumer market and the increasing requirements of consumers for the quality and performance of footwear, high-peeling footwear materials have shown considerable market prospects. In the manufacture of sports shoes, labor protection shoes and various functional shoes, high-peeling footwear materials have become a key factor for many shoe companies to improve their product competitiveness due to their excellent wear resistance, strong adhesion and good physical and mechanical properties, and the market demand has shown a steady growth trend. However, at a time when environmental awareness is gradually awakening and becoming a global consensus, most high-peeling footwear materials are in an environmental dilemma. In terms of the selection of raw materials, many high-peeling footwear materials rely on petroleum-based raw materials. Their mining and processing processes not only consume a lot of energy, but are also accompanied by greenhouse gas emissions and potential damage to the ecological environment. Subsequent waste treatment is also difficult to achieve efficient recycling and recycling due to the complex structure and composition of the materials. A large amount of waste footwear materials or landfills will occupy land resources and may pollute the soil, or incineration will produce toxic and harmful gases that are emitted into the atmosphere, further exacerbating environmental pressure.
[0003] The main raw materials of bio-based polyurethane materials are renewable biomass, such as crops, plant fibers, etc., which produce less greenhouse gases and pollutants during the production process. Moreover, these materials are biodegradable and can be decomposed into harmless substances in the natural environment after the end of their service life. They will not cause long-term environmental pollution like traditional petroleum-based polyurethane materials, which will help reduce the pressure on waste and landfills. However, some bio-based polyurethane materials themselves have low cohesive energy and weak intermolecular forces, which affects their bonding performance with other materials after they are made into shoe materials, resulting in low peel strength. For example, some starch-based bio-based materials have relatively simple molecular structures and lack sufficient active groups to form strong chemical bonds or physical entanglements, which in turn affects the peel strength.
[0004] At present, most high-peeling shoe materials also face many limitations in terms of waterproof and oil-proof. First, from the perspective of the material's own structure, the microscopic pore structure of high-peeling shoe materials is relatively large and complex, which makes it easy for water molecules and oil molecules to invade the interior of the material and difficult to form an effective barrier layer on the surface, resulting in its inherent lack of waterproof and oil-proof performance; secondly, in terms of production technology, the existing processing process mainly focuses on improving the mechanical properties of shoe materials such as peeling strength, but not enough attention is paid to the waterproof and oil-proof function, lacking effective surface treatment technology or adding corresponding functional additives to improve its waterproof and oil-proof performance; thirdly, the compatibility between high-peeling shoe materials and waterproof and oil-proof finishing agents is poor. When performing waterproof and oil-proof finishing, the finishing agent is difficult to evenly adhere to the surface of the shoe material or fully penetrate into the internal pores, affecting the durability and stability of the waterproof and oil-proof effect. Summary of the invention
[0005] In order to solve the technical problem that synthetic leather has poor waterproof and oil-proof performance, a waterproof and oil-proof high-stripping environmentally friendly shoe material and a preparation method thereof are provided. The invention uses a silane coupling agent to pretreat a polyethylene terephthalate base fabric, forms a polyurethane coating on the surface, and then uses a surrounding airflow ultrasonic atomization to treat the surface, thereby obtaining a high-stripping environmentally friendly shoe material with outstanding waterproof and oil-proof performance.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A method for preparing a waterproof, oil-proof, highly releasable and environmentally friendly shoe material comprises the following steps:
[0008] (1) soaking a polyethylene terephthalate base fabric in a base fabric treatment liquid, taking it out, squeezing it, and then drying it; the base fabric treatment liquid is a silane coupling agent hydrolyzate;
[0009] Then, the base fabric is immersed in the impregnation liquid, taken out and squeezed, immersed in the pre-coagulation bath for coagulation, extruded again to control the liquid content, coated with bio-based polyurethane slurry, allowed to stand, immersed in the coagulation bath to make the bio-based polyurethane slurry on the surface of the base fabric coagulate to form a polyurethane coating, and then washed with water and dried to obtain the base fabric;
[0010] (2) The base surface treatment liquid is deposited on the preheated base surface through the surrounding airflow ultrasonic atomization effect, and then left to stand and dried to obtain a waterproof, oil-proof, highly peelable and environmentally friendly shoe material.
[0011] Furthermore, the method for obtaining the silane coupling agent hydrolyzate is as follows: adding the silane coupling agent to N,N-dimethylformamide, stirring for 1-2 minutes, adding deionized water dropwise, continuing to stir for 1-2 minutes, then adding acetic acid to adjust the pH value of the solution to between 4 and 5, and stirring for 10-20 minutes;
[0012] Wherein, the mass ratio of N,N-dimethylformamide, silane coupling agent and deionized water is 10:0.1-1:0.1;
[0013] The silane coupling agent is selected from γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and / or γ-aminopropyltriethoxysilane.
[0014] Furthermore, the polyethylene terephthalate base fabric is immersed in the base fabric treatment liquid for 30-60 minutes, and the drying temperature after being taken out and squeezed is 100-120°C.
[0015] The impregnation liquid comprises the following materials by weight: 350-400 parts of DMF, 30-40 parts of a hard polyurethane resin with a solid content of 25wt%-35wt%, 60-70 parts of a soft polyurethane resin with a solid content of 25wt%-35wt%, and 10-30 parts of a black paste; wherein the hard polyurethane resin has a viscosity of 80-160 Pa·s at 25°C and a modulus of 220-160 kg / cm at 100%. 2 , tensile strength at least 400kg / cm 2 , an elongation of at least 200%, and a highly rigid, fluorine-free, hydrolysis-resistant wet-process polyurethane impregnated resin having excellent film-forming properties and hydrolysis resistance; wherein the soft polyurethane resin has a viscosity of 20-80 Pa·s at 25°C and a modulus of 100% of 10-20 kg / cm 2 , tensile strength at least 50kg / cm 2 , the elongation is at least 700%, it is an ultra-soft high tear polyurethane impregnated resin, it has excellent elongation performance, good affinity to PET materials, and can improve the tear strength;
[0016] The bio-based polyurethane slurry comprises the following materials by weight: 40-55 parts of DMF, 0.3-0.8 parts of paper powder, 10-20 parts of extra-white light calcium carbonate, 80-150 parts of bio-based polyurethane resin with a solid content of 28wt%-38wt%, and 1-10 parts of black pulp; wherein the bio-based polyurethane resin has a viscosity of 150-350 Pa·s at 25°C and a modulus of 100% of 100kg / cm 2 , tensile strength at least 300kg / cm 2 , elongation of at least 300%, is a medium-hard, hydrolysis-resistant bio-based polyurethane wet resin with the advantages of medium hardness, good film-forming properties, good hydrolysis resistance, and high peel strength. The theoretical bio-based content is 40%.
[0017] Furthermore, the pre-coagulation bath is a DMF aqueous solution with a mass fraction of 25%-45%, the coagulation time is 10-15 minutes, and the extrusion pressure for controlling the liquid content is 2-6kg, and the liquid content is in the range of 30-60wt%.
[0018] Furthermore, the coating thickness of the bio-based polyurethane slurry on the surface of the base fabric is within the range of 1-3 mm, the standing time after coating is 1-2 min, and the coagulation bath is a DMF aqueous solution with a mass fraction of 18%-28%. The main raw materials of bio-based polyurethane come from biomass, such as soybean oil, castor oil, palm oil, corn starch, etc. These biomass resources are widely available and can be regenerated through natural processes, which can effectively reduce dependence on non-renewable resources and help alleviate the problem of resource shortage.
[0019] Furthermore, after the polyurethane coating is formed, it is washed with clean water, then extruded in the range of 1-5 kg, and the washing-extrusion operation is repeated 30-60 times, and then dried in the range of 120° C.-150° C. for 10-30 minutes to obtain the bass.
[0020] Furthermore, the BESS surface treatment liquid is an aqueous acrylic emulsion obtained by diluting an acrylic emulsion with deionized water, and the mass fraction of the aqueous acrylic emulsion obtained by dilution is in the range of 0.1%-50%.
[0021] Furthermore, the deposition of water-based acrylic emulsion by surrounding airflow ultrasonic atomization is performed by using a surrounding airflow ultrasonic atomization device, which includes an ultrasonic nozzle. The ultrasonic nozzle is movable, and the end of the ultrasonic nozzle has a liquid outlet and a plurality of carrier gas outlets uniformly arranged around the liquid outlet. The number of the carrier gas outlets is at least two, and the carrier gas in the carrier gas outlet is nitrogen. The ultrasonic power of the ultrasonic nozzle is 2W, the liquid inlet flow rate of the water-based acrylic emulsion is 0.1-1mL / min, the single-pass spraying step distance of the ultrasonic nozzle is 0.5-5mm, the distance between the ultrasonic nozzle and the base is 3cm, and the base is preheated before deposition, and the preheating temperature of the base is 30-60°C.
[0022] Another aspect of the present invention provides a waterproof, oil-proof, highly releasable, and environmentally friendly shoe material obtained by the above-mentioned preparation method.
[0023] Beneficial technical effects: The present invention uses a silane coupling agent to pretreat a polyethylene terephthalate (PET) base fabric with a relatively smooth surface and relatively stable chemical properties, and selects a silane coupling agent with an amino group and / or an epoxy group, and the amino group and / or the epoxy group form a hydrogen bond or a condensation reaction with the hydroxyl group of the PET base fabric, thereby forming a chemical bond on the surface of the PET base fabric; at the same time, the organic functional group of the silane coupling agent can be better compatible with other organic materials or coatings added subsequently, effectively improving the interface compatibility between the PET base fabric and these materials, and enhancing the bonding force between them; through the action of the silane coupling agent, the bonding between the PET base fabric and other materials is made stronger, and when subjected to external force, stress can be more effectively transmitted, thereby improving the mechanical properties of the composite material, such as tensile strength, tear strength, wear resistance, etc.;
[0024] The present invention utilizes the ultrasonic atomization effect of surrounding airflow to deposit an aqueous acrylic solution on the surface of a bass at a certain temperature. By controlling the number of carrier gas buckles, the movement state of the aqueous acrylic solution to the bass and the spreading state on the surface of the bass can be more accurately controlled. After standing and drying, an ultra-thin coating with a more uniform thickness is formed, which can effectively improve the waterproof and oil-proof performance of the bass. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the ultrasonic atomization deposition of the surrounding airflow in the method for preparing the waterproof, oil-proof and highly peelable environmentally friendly shoe material of the present invention;
[0026] Figure 2 This is a schematic diagram of ultrasonic atomization deposition in the method for preparing environmentally friendly shoe materials in Comparative Example 6. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
[0028] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0029] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0030] The thickness of the PET base fabric used below is 0.6mm and the weight is 160g / m 2 Silane coupling agent was purchased from Dongguan Shanyi Plastic Chemical Co., Ltd.; the surrounding airflow ultrasonic atomization device was purchased from Beijing Dongfang Jinrong Ultrasonic Electric Co., Ltd.; the acrylic emulsion model used was 6916 or etersol6916, with an original mass fraction of 60wt%, from Changxing Materials Industry Co., Ltd.
[0031] Example 1
[0032] A method for preparing a waterproof, oil-proof, highly releasable and environmentally friendly shoe material comprises the following steps:
[0033] (1) Preparation of base fabric treatment liquid: Add 5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 100 g of DMF, stir for 1 min, then drop 1 g of deionized water and stir for 1 min, add acetic acid to adjust the solution pH to 5, and stir for another 15 min to obtain a silane coupling agent hydrolyzate;
[0034] The PET base fabric is soaked in the silane coupling agent hydrolyzate for 30 minutes, taken out, squeezed and dried at 120°C; after drying, the PET base fabric is soaked in the impregnation solution (completely soaked), taken out and squeezed with a 6kg pressure, and then immersed in a pre-coagulation bath for coagulation for 15 minutes, the pre-coagulation bath is a 45wt% DMF aqueous solution, taken out and squeezed after coagulation, and the liquid content is controlled to be 55wt%;
[0035] Then, the surface was coated with bio-based polyurethane slurry with a coating thickness of 1.2 mm, and after standing for 1 minute, it was immersed in a coagulation bath to solidify the bio-based polyurethane slurry on the surface of the base fabric to form a polyurethane coating. The coagulation bath was a 22 wt% DMF aqueous solution, and then washed with clean water, squeezed with a pressure of 4 kg, and the washing-squeezing operation was repeated 50 times, and then dried at 150° C. for 15 minutes to obtain the base fabric;
[0036] The impregnation liquid formula is as follows: DMF 380g, hard polyurethane resin model HDD-9240HNF 35g (high hardness fluorine-free hydrolysis-resistant wet polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 80-160Pa·s at 25°C and a modulus of 220-160kg / cm at 100%). 2 , tensile strength at least 400kg / cm 2 , elongation of at least 200%, the solvent in the resin is DMF), 65g of soft polyurethane resin model HDD-3008H (super soft high tear polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 20-80Pa·s at 25℃ and a modulus of 100% of 10-20kg / cm 2 , tensile strength at least 50kg / cm 2 , elongation of at least 700%, the solvent in the resin is DMF), black paste 20g;
[0037] The formula of bio-based polyurethane slurry is as follows: DMF 45g, paper powder 0.5g, extra white light calcium carbonate 15g (whiteness greater than 95%, sedimentation volume 2.4-2.8mL / g, powder particle size less than 1200 mesh), HDW-3104H-BIO bio-based polyurethane resin 100g (a medium-hard hydrolysis-resistant bio-based polyurethane wet resin with a solid content of 31-33wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 150-350Pa·s at 25°C and a modulus of 100% of 100kg / cm 2 , tensile strength at least 300kg / cm 2 , elongation at least 300%), black pulp 5g;
[0038] (2) Preparation of the Besse surface treatment solution: add 10 g of acrylic emulsion to 90 g of deionized water and stir for 2 min to obtain a diluted aqueous acrylic emulsion;
[0039] The aqueous acrylic emulsion is deposited on the preheated bass surface by surrounding airflow ultrasonic atomization. The deposition is carried out using a surrounding airflow ultrasonic atomization device. The deposition process is as follows: Figure 1 As shown, the surrounding airflow ultrasonic atomization device includes a syringe and an ultrasonic nozzle, the water-based acrylic emulsion is injected into the syringe, the liquid feeding speed is 0.5mL / min, the ultrasonic nozzle can move, the end of the ultrasonic nozzle has a liquid outlet and four carrier gas ports uniformly arranged around the liquid outlet, the carrier gas in the carrier gas port is nitrogen, the ultrasonic power of the ultrasonic nozzle is 2W, the single-pass spraying step of the ultrasonic nozzle is 1mm, the distance between the ultrasonic nozzle and the base is 3cm, the base is preheated before deposition, and the preheating temperature of the base is 50°C. The water-based acrylic emulsion is evenly dispersed into tiny droplets by ultrasonic action, and enters the deposition chamber with the nitrogen of the carrier gas from the liquid outlet, and the water-based acrylic emulsion droplets are evenly deposited on the surface of the base. After the deposition is completed, the solvent is allowed to evaporate for 1min, and it is dried at 120°C for 15min to obtain a waterproof, oil-proof, highly peelable and environmentally friendly shoe material.
[0040] Example 2
[0041] A method for preparing a waterproof, oil-proof, highly releasable and environmentally friendly shoe material comprises the following steps:
[0042] (1) Preparation of base fabric treatment solution: Add 10 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 100 g of DMF, stir for 1 min, then drop 1 g of deionized water and stir for 1 min, add acetic acid to adjust the solution pH to 4, and stir for another 15 min to obtain a silane coupling agent hydrolyzate;
[0043] The PET base fabric is soaked in the silane coupling agent hydrolyzate for 30 minutes, taken out, squeezed and dried at 120°C; after drying, the PET base fabric is soaked in the impregnation solution (completely soaked), taken out and squeezed with a 6kg pressure, and then immersed in a pre-coagulation bath for coagulation for 15 minutes, the pre-coagulation bath is a 45wt% DMF aqueous solution, taken out and squeezed after coagulation, and the liquid content is controlled to be 55wt%;
[0044] Then, the surface was coated with bio-based polyurethane slurry with a coating thickness of 1.2 mm, and after standing for 1 minute, it was immersed in a coagulation bath to solidify the bio-based polyurethane slurry on the surface of the base fabric to form a polyurethane coating. The coagulation bath was a 22 wt% DMF aqueous solution, and then washed with clean water, squeezed with a pressure of 4 kg, and the washing-squeezing operation was repeated 50 times, and then dried at 150° C. for 15 minutes to obtain the base fabric;
[0045] The impregnation liquid formula is as follows: DMF 380g, hard polyurethane resin model HDD-9240HNF 35g (high hardness fluorine-free hydrolysis-resistant wet polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 80-160Pa·s at 25°C and a modulus of 220-160kg / cm at 100%). 2 , tensile strength at least 400kg / cm 2 , elongation of at least 200%, the solvent in the resin is DMF), 65g of soft polyurethane resin model HDD-3008H (super soft high tear polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 20-80Pa·s at 25℃ and a modulus of 100% of 10-20kg / cm 2 , tensile strength at least 50kg / cm 2 , elongation of at least 700%, the solvent in the resin is DMF), black paste 20g;
[0046] The formula of bio-based polyurethane slurry is as follows: DMF 45g, paper powder 0.5g, extra white light calcium carbonate 15g (whiteness greater than 95%, sedimentation volume 2.4-2.8mL / g, powder particle size less than 1200 mesh), HDW-3104H-BIO bio-based polyurethane resin 100g (a medium-hard hydrolysis-resistant bio-based polyurethane wet resin with a solid content of 31-33wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 150-350Pa·s at 25°C and a modulus of 100% of 100kg / cm 2 , tensile strength at least 300kg / cm 2 , elongation at least 300%), black pulp 5g;
[0047] (2) Preparation of the Besse surface treatment solution: Add 50 g of acrylic emulsion to 50 g of deionized water and stir for 2 min to obtain a diluted aqueous acrylic emulsion;
[0048] The aqueous acrylic emulsion is deposited on the preheated bass surface by surrounding airflow ultrasonic atomization. The deposition is carried out using a surrounding airflow ultrasonic atomization device. The deposition process is as follows: Figure 1 As shown, the surrounding airflow ultrasonic atomization device includes a syringe and an ultrasonic nozzle, the water-based acrylic emulsion is injected into the syringe, the liquid feeding speed is 0.1mL / min, the ultrasonic nozzle can move, the end of the ultrasonic nozzle has a liquid outlet and four carrier gas ports uniformly arranged around the liquid outlet, the carrier gas in the carrier gas port is nitrogen, the ultrasonic power of the ultrasonic nozzle is 2W, the single-pass spraying step of the ultrasonic nozzle is 1mm, the distance between the ultrasonic nozzle and the base is 3cm, the base is preheated before deposition, and the preheating temperature of the base is 30°C. The water-based acrylic emulsion is evenly dispersed into tiny droplets by ultrasonic action, and enters the deposition chamber from the liquid outlet with the nitrogen of the carrier gas buckle, and the water-based acrylic emulsion droplets are evenly deposited on the surface of the base. After the deposition is completed, the solvent is allowed to evaporate for 1min, and it is dried at 120°C for 15min to obtain a waterproof, oil-proof, highly peelable and environmentally friendly shoe material.
[0049] Example 3
[0050] A method for preparing a waterproof, oil-proof, highly releasable and environmentally friendly shoe material comprises the following steps:
[0051] (1) Preparation of base fabric treatment solution: Add 5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 100 g of DMF, stir for 1 min, then drop 1 g of deionized water and stir for 1 min, add acetic acid to adjust the solution pH to 4, and stir for another 15 min to obtain a silane coupling agent hydrolyzate;
[0052] The PET base fabric is soaked in the silane coupling agent hydrolyzate for 30 minutes, taken out, squeezed and dried at 120°C; after drying, the PET base fabric is soaked in the impregnation solution (completely soaked), taken out and squeezed with a 6kg pressure, and then immersed in a pre-coagulation bath for coagulation for 15 minutes, the pre-coagulation bath is a 45wt% DMF aqueous solution, taken out and squeezed after coagulation, and the liquid content is controlled to be 45wt%;
[0053] Then, the surface was coated with bio-based polyurethane slurry with a coating thickness of 1.2 mm, and after standing for 1 minute, it was immersed in a coagulation bath to solidify the bio-based polyurethane slurry on the surface of the base fabric to form a polyurethane coating. The coagulation bath was a 22 wt% DMF aqueous solution, and then washed with clean water, squeezed with a pressure of 4 kg, and the washing-squeezing operation was repeated 50 times, and then dried at 150° C. for 15 minutes to obtain the base fabric;
[0054] The impregnation liquid formula is as follows: DMF 380g, hard polyurethane resin model HDD-9240HNF 35g (high hardness fluorine-free hydrolysis-resistant wet polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 80-160Pa·s at 25°C and a modulus of 220-160kg / cm at 100%). 2 , tensile strength at least 400kg / cm 2 , elongation of at least 200%, the solvent in the resin is DMF), 65g of soft polyurethane resin model HDD-3008H (super soft high tear polyurethane impregnation resin, solid content 29-31wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 20-80Pa·s at 25℃ and a modulus of 100% of 10-20kg / cm 2 , tensile strength at least 50kg / cm 2 , elongation of at least 700%, the solvent in the resin is DMF), black paste 20g;
[0055] The formula of bio-based polyurethane slurry is as follows: DMF 45g, paper powder 0.5g, extra white light calcium carbonate 15g (whiteness greater than 95%, sedimentation volume 2.4-2.8mL / g, powder particle size less than 1200 mesh), HDW-3104H-BIO bio-based polyurethane resin 100g (a medium-hard hydrolysis-resistant bio-based polyurethane wet resin with a solid content of 31-33wt%, provided by Shanghai Huide Technology Co., Ltd., with a viscosity of 150-350Pa·s at 25°C and a modulus of 100% of 100kg / cm 2 , tensile strength at least 300kg / cm 2 , elongation at least 300%), black pulp 5g;
[0056] (2) Preparation of the Besse surface treatment solution: add 10 g of acrylic emulsion to 90 g of deionized water and stir for 2 min to obtain a diluted aqueous acrylic emulsion;
[0057] The aqueous acrylic emulsion is deposited on the preheated bass surface by surrounding airflow ultrasonic atomization. The deposition is carried out using a surrounding airflow ultrasonic atomization device. The deposition process is as follows: Figure 1As shown, the surrounding airflow ultrasonic atomization device includes a syringe and an ultrasonic nozzle, the water-based acrylic emulsion is injected into the syringe, the liquid feeding speed is 0.5mL / min, the ultrasonic nozzle can move, the end of the ultrasonic nozzle has a liquid outlet and four carrier gas ports uniformly arranged around the liquid outlet, the carrier gas in the carrier gas port is nitrogen, the ultrasonic power of the ultrasonic nozzle is 2W, the single-pass spraying step of the ultrasonic nozzle is 1mm, the distance between the ultrasonic nozzle and the base is 3cm, the base is preheated before deposition, and the preheating temperature of the base is 50°C. The water-based acrylic emulsion is evenly dispersed into tiny droplets by ultrasonic action, and enters the deposition chamber with the nitrogen of the carrier gas from the liquid outlet, and the water-based acrylic emulsion droplets are evenly deposited on the surface of the base. After the deposition is completed, the solvent is allowed to evaporate for 1min, and it is dried at 120°C for 15min to obtain a waterproof, oil-proof, highly peelable and environmentally friendly shoe material.
[0058] Comparative Example 1
[0059] The preparation method of synthetic leather in this case is as follows:
[0060] (1) The PET base fabric is directly immersed in the impregnation liquid (completely immersed), taken out and squeezed with a 6 kg pressure, and then immersed in a pre-coagulation bath for coagulation for 15 minutes. The pre-coagulation bath is a 45 wt % DMF aqueous solution. After coagulation, it is taken out and squeezed, and the liquid content is controlled to be 55 wt %;
[0061] Then, the surface was coated with bio-based polyurethane slurry with a coating thickness of 1.2 mm, and after standing for 1 minute, it was immersed in a coagulation bath to solidify the bio-based polyurethane slurry on the surface of the base fabric to form a polyurethane coating. The coagulation bath was a 22 wt% DMF aqueous solution, and then washed with clean water, squeezed with a pressure of 4 kg, and the washing-squeezing operation was repeated 50 times, and then dried at 150° C. for 15 minutes to obtain the base fabric;
[0062] (2) The specific operation is the same as step (2) of Example 1.
[0063] Comparative Example 2
[0064] The preparation method of synthetic leather in this case is as follows:
[0065] (1) The specific operation is the same as step (1) of Example 1;
[0066] (2) Preparation of water-based acrylic emulsion: add 10 g of acrylic emulsion to 90 g of deionized water and stir for 2 min; directly apply the water-based acrylic emulsion on the surface of the bass, let it stand for 1 min, and dry it at 120°C for 15 min.
[0067] Comparative Example 3
[0068] The method for preparing synthetic leather in this case is the same as that in Example 1, except that step (2) is not present. In this case, only bass is prepared.
[0069] Comparative Example 4
[0070] The method for preparing synthetic leather in this case is the same as that in Example 1, except that in step (2), an acrylic emulsion with an original mass fraction of 60% (without dilution) is directly used.
[0071] Comparative Example 5
[0072] The method for preparing synthetic leather in this case is the same as that in Example 1, except that the bio-based polyurethane slurry in step (1) is replaced with conventional polyurethane slurry;
[0073] The formula of conventional polyurethane slurry is as follows: DMF 45g, paper powder 0.5g, extra white light calcium carbonate 15g (same parameters as Example 1), model XCW-3590H two-step wet polyurethane resin for ordinary leather 100g (solid content 34-36wt%, provided by Asahikawa Chemical (Suzhou) Co., Ltd., with a viscosity of 220-260Pa·s at 25°C, a modulus of 8-10MPa, and a tensile strength of more than 30MPa), and black slurry 5g.
[0074] Comparative Example 6
[0075] The method for preparing synthetic leather in this case is the same as that in Example 1, except that the number of carrier gas ports on the ultrasonic nozzle of the surrounding airflow ultrasonic atomization device in step (2) is 1, as shown in detail. Figure 2 shown.
[0076] The latitudinal peeling of the shoe material, the latitudinal peeling after immersion in the degradation enzyme and potassium dihydrogen phosphate / dipotassium hydrogen phosphate buffer solution for 24 hours, the water contact angle, and the oil contact angle are compared. The measurement results are shown in Table 1.
[0077] The weft peeling test standard refers to GB / T 16799-2008; the water contact angle test standard refers to ISO / TS14778:2021; the oil contact angle test standard refers to ISO / TS14778:2021.
[0078] The latitudinal peeling test method after immersion of 24h degradation enzyme in potassium dihydrogen phosphate / dipotassium hydrogen phosphate buffer solution is as follows:
[0079] 1. Rinse a leather sample with a width of 3 cm and a mass of 2 g with distilled water to remove impurities on the surface, and then dry it in an oven at about 40°C to constant weight;
[0080] 2. Prepare potassium dihydrogen phosphate / dipotassium hydrogen phosphate buffer solution (pH = 8.5);
[0081] 3. Dissolve the protease in buffer at a concentration of 0.4% (mass / volume ratio);
[0082] 4. Place the leather sample in a conical flask and add 200g of enzyme solution to the conical flask, making sure the leather sample is completely immersed in the enzyme solution;
[0083] 5. Place the conical flask in a 25°C constant temperature incubator for 24 hours;
[0084] 6. Take out the leather sample, rinse it with distilled water, and dry it in an oven to constant weight;
[0085] 7. Measure the weft peeling (test standard: GB / T 16799-2008).
[0086] Table 1 Shoe material performance of each case
[0087]
[0088] As can be seen from Table 1, in combination with Example 1 and Comparative Example 1, when the base fabric is not treated with the base fabric treatment liquid, the weft peeling of the shoe material and the weft peeling after immersion in the degradation enzyme and potassium dihydrogen phosphate / dipotassium hydrogen phosphate buffer solution for 24 hours are relatively low, which verifies that the base fabric treatment liquid can increase the bonding force between the PU layer and the base fabric;
[0089] Combining Example 1 and Comparative Example 2, it can be seen that compared with the ultrasonic atomization deposition method, scraping the Bass surface treatment liquid on the Bass surface will make the coating thickness uneven, thereby reducing the water contact angle and the oil contact angle, which verifies that the ultrasonic atomization deposition method can improve the surface smoothness of the coating;
[0090] Combining Example 1 and Comparative Example 3, it can be seen that compared with depositing the treatment liquid on the surface of the base, the water contact angle and oil contact angle of the base without depositing the treatment liquid are smaller, which verifies that the deposited treatment liquid can improve the waterproof and oil-proof performance of the shoe material;
[0091] Combining Example 1 and Comparative Example 4, it can be seen that compared with the diluted BASS surface treatment liquid, the undiluted surface treatment liquid cannot be dispersed evenly under a certain power of the ultrasonic nozzle, resulting in the undiluted surface treatment liquid not being able to spread evenly on the BASS surface, thereby resulting in smaller water contact angles and oil contact angles, verifying that an excessively high concentration of the BASS surface treatment liquid is not conducive to improving the waterproof and oil-proof properties of the shoe material;
[0092] Combining Example 1 and Comparative Example 5, it can be seen that the shoe material of Comparative Example 5 has a higher latitudinal peeling after being soaked in the degradation enzyme and potassium dihydrogen phosphate / dipotassium hydrogen phosphate buffer solution for 24 hours, which verifies that the bio-based polyurethane material has good degradability.
[0093] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material, characterized in that: The steps include: (1) soaking a polyethylene terephthalate base fabric in a base fabric treatment liquid, taking it out, squeezing it, and then drying it; the base fabric treatment liquid is a silane coupling agent hydrolyzate; Then, the base fabric is immersed in the impregnation liquid, taken out and squeezed, immersed in the pre-coagulation bath for coagulation, extruded again to control the liquid content, coated with bio-based polyurethane slurry, allowed to stand, immersed in the coagulation bath to make the bio-based polyurethane slurry on the surface of the base fabric coagulate to form a polyurethane coating, and then washed with water and dried to obtain the base fabric; (2) The base surface treatment liquid is deposited on the preheated base surface through the surrounding airflow ultrasonic atomization effect, and then allowed to stand and dry to obtain a waterproof, oil-proof, highly peelable and environmentally friendly shoe material.
2. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The method for obtaining the silane coupling agent hydrolyzate is as follows: adding the silane coupling agent to N,N-dimethylformamide, stirring for 1-2 minutes, adding deionized water dropwise, continuing to stir for 1-2 minutes, then adding acetic acid to adjust the pH value of the solution to between 4 and 5, and stirring for 10-20 minutes; Wherein, the mass ratio of N,N-dimethylformamide, silane coupling agent and deionized water is 10:0.1-1:0.1; The silane coupling agent is selected from γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and / or γ-aminopropyltriethoxysilane.
3. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The polyethylene terephthalate base fabric is immersed in the base fabric treatment liquid for 30-60 minutes, and the drying temperature after being taken out and squeezed is 100-120°C.
4. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The impregnation liquid comprises the following materials by weight: 350-400 parts of DMF, 30-40 parts of a hard polyurethane resin with a solid content of 25wt%-35wt%, 60-70 parts of a soft polyurethane resin with a solid content of 25wt%-35wt%, and 10-30 parts of a black paste; wherein the hard polyurethane resin has a viscosity of 80-160 Pa·s at 25°C and a modulus of 220-160 kg / cm at 100%. 2 , tensile strength at least 400kg / cm 2 , an elongation of at least 200%; wherein the soft polyurethane resin has a viscosity of 20-80 Pa·s at 25°C and a modulus of 100% of 10-20 kg / cm 2 , tensile strength at least 50kg / cm 2 , elongation at least 700%; The bio-based polyurethane slurry comprises the following materials by weight: 40-55 parts of DMF, 0.3-0.8 parts of paper powder, 10-20 parts of extra-white light calcium carbonate, 80-150 parts of bio-based polyurethane resin with a solid content of 28wt%-38wt%, and 1-10 parts of black pulp; wherein the bio-based polyurethane resin has a viscosity of 150-350 Pa·s at 25°C and a modulus of 100% of 100kg / cm 2 , tensile strength at least 300kg / cm 2 , elongation at least 300%.
5. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The pre-coagulation bath is a DMF aqueous solution with a mass fraction of 25%-45%, the coagulation time is 10-15 minutes, and the extrusion pressure for controlling the liquid content is 2-6kg and the liquid content is within the range of 30-60wt%.
6. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The coating thickness of the bio-based polyurethane slurry on the surface of the base fabric is in the range of 1-3 mm, the standing time after coating is 1-2 minutes, and the coagulation bath is a DMF aqueous solution with a mass fraction of 18%-28%.
7. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: After the polyurethane coating is formed, it is washed with clean water, and then extruded in the range of 1-5kg, and the washing-extrusion operation is repeated 30-60 times, and then dried in the range of 120℃-150℃ for 10-30min to obtain the base.
8. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: The BESS surface treatment liquid is a water-based acrylic emulsion obtained by diluting acrylic emulsion with deionized water, and the mass fraction of the water-based acrylic emulsion obtained by dilution is in the range of 0.1%-50%.
9. The method for preparing a waterproof, oil-proof, highly peelable and environmentally friendly shoe material according to claim 1, characterized in that: Surrounding airflow ultrasonic atomization is used to deposit water-based acrylic emulsion. The surrounding airflow ultrasonic atomization device is used for deposition. The surrounding airflow ultrasonic atomization device includes an ultrasonic nozzle. The ultrasonic nozzle can move. The end of the ultrasonic nozzle has a liquid outlet and multiple carrier gas ports uniformly arranged around the liquid outlet. The number of the carrier gas ports is at least two. The carrier gas in the carrier gas ports is nitrogen. The ultrasonic power of the ultrasonic nozzle is 2W, the liquid inlet flow rate of the water-based acrylic emulsion is 0.1-1mL / min, the single-pass spraying step distance of the ultrasonic nozzle is 0.5-5mm, the distance between the ultrasonic nozzle and the base is 3cm, and the base is preheated before deposition. The preheating temperature of the base is 30-60℃.
10. The waterproof, oil-proof, highly strippable and environmentally friendly shoe material obtained by the preparation method according to any one of claims 1 to 9.